Limits on the production of the standard model Higgs boson in pp collisions at root s=7 TeV with the ATLAS detector - Onofre, A. (2011)
A search for the Standard Model Higgs boson at the Large Hadron Collider (LHC) running at a centre-of-mass energy of 7 TeV is reported, based on a total integrated luminosity of up to 40 pb−1 collected by the ATLAS detector in 2010. Several Higgs boson decay channels: H→γγ, H→ZZ(∗)→ℓℓℓℓ, H→ZZ→ℓℓνν, H→ZZ→ℓℓqq, H→WW(∗)→ℓνℓν and H→WW→ℓνqq (ℓ is e, μ) are combined in a mass range from 110 GeV to 600 GeV. The highest sensitivity is achieved in the mass range between 160 GeV and 170 GeV, where the expected 95% CL exclusion sensitivity is at Higgs boson production cross sections 2.3 times the Standard Model prediction. Upper limits on the cross section for its production are determined. Models with a fourth generation of heavy leptons and quarks with Standard Model-like couplings to the Higgs boson are also investigated and are excluded at 95% CL for a Higgs boson mass in the range from 140 GeV to 185 GeV.